Pembangunan Komuniti Melalui Inisiatif Tanggungjawab Sosial Korporat (Csr): Kajian Pengalaman Peserta Projek Perladangan Cili Kontrak Di Bukit Awang, Pasir Puteh, Kelantan - Sum, Sarmila Md (2013)
Corporate Social Responsibility (CSR) initiative has been provided as a source for the corporation to contribute together in community development. In this regard, the purpose of this research is to study and identify the experience of the community involved as participants in a CSR initiative project and to analyze how the CSR initiative project undertaken has helped the development of the community. A total of 45 participants of a CSR initiative chilli contract farming project undertaken at Bukit Awang, Pasir Puteh, Kelantan has been selected through the theoretical purposive sampling method as respondents for the research. This interpretive research analyses personal experience narratives of the CSR initiative project’s participants obtained through the method of face-to-face interviews. A total of 110 basic themes (TA) has been identified as a the result of thematic analysis which depicting 22 main themes (MT) of the farmers experience as the community involved in the CSR contract farming project. Based on the said main themes, eight categories of community development process and outcome components have been identified comprising 1) human capital, 2) social capital, 3) support by development agency 4) capacity building, 5) support by corporation, 6) social well-being, 7) economic well-being and 8) empowerment building.